Answer:
√190
Explanation:
In the figure , there are 2 right angled triangles with a common perpendicular & both the triangles combine to form a new right angled triangle.
Let the triangle with 9 as base be T¹ & Let the triangle with base 10 be T². Let the triangle formed by T¹ & T² be T³.
In T² ,
Hypotenuse = y
Base = 10
According to Pythagorean Theorem ,
(Hypotenuse)² = (Base)² + (Perpendicular)²
Hence, (Perpendicular)² =
![y^2 - 10^2 = y^2 - 100](https://img.qammunity.org/2021/formulas/mathematics/college/5yy6gtdz9bszwzamhmdb9smdlwge0t9k0a.png)
In T¹ ,
Perpendicular =
(∵ Both T¹ & T² have common perpendicular)
⇒(Perpendicular)² =
![y^2 - 100](https://img.qammunity.org/2021/formulas/mathematics/college/m1k6oexq5ex764m4rf2e7j7kgzjp2xs7qo.png)
Base = 9
⇒ (Base)² = 9²
Hypotenuse =
Using Pythagorean Theorem ,
(Hypotenuse)² = (Perpendicular)² + (Base)²
⇒ (Hypotenuse)² =
.............................................eqn.2
Now in T³ ,
Base = y
⇒ (Base)² = y²
Perpendicular =
(∵Perpendicular of T³ = Hypotenuse of T²)
⇒ (Perpendicular)² =
![(√((y^2 - 100) + 9^2))^2= (y^2 - 100) + 81 = y^2 - 19](https://img.qammunity.org/2021/formulas/mathematics/college/6nq91043tyw9jm6m2lebmrj2t8h8lrl3i8.png)
Hypotenuse = 9 + 10 = 19
Using Pythagorean Theorem ,
(Hypotenuse)² = (Perpendicular)² + (Base)²
![=> 19^2 = y^2 - 19 + y^2\\\\=> 2y^2 = 19^2 + 19 = 19(19 + 1) = 19*20\\\\=> y^2 = (19*20)/(2) = 19*10 = 190\\ \\=> y =√(190)](https://img.qammunity.org/2021/formulas/mathematics/college/k4bcbdo55xr8r92ay8wit0exatbxwpw08l.png)